Pre‐ and post‐treatment blood‐based genomic landscape of patients with ROS1 or NTRK fusion‐positive solid tumours treated with entrectinib. Issue 10 (22nd April 2022) - Dziadziuszko, Rafal; Hung, Tiffany; Wang, Kun; Choeurng, Voleak; Drilon, Alexander; Doebele, Robert C.; Barlesi, Fabrice; Wu, Charlie; Dennis, Lucas; Skoletsky, Joel; Woodhouse, Ryan; Li, Meijuan; et al.
Abstract : Genomic tumour profiling informs targeted treatment options. Entrectinib is a tyrosine kinase inhibitor with efficacy in NTRK fusion‐positive (‐fp) solid tumours and ROS1 ‐fp non‐small cell lung cancer. FoundationOne® Liquid CDx (F1L CDx), a non‐invasive in vitro next‐generation sequencing (NGS)‐based diagnostic, detects genomic alterations in plasma circulating tumour DNA (ctDNA). We evaluated the clinical validity of F1L CDx as an aid in identifying patients with NTRK ‐fp or ROS1 ‐fp tumours and assessed the genomic landscape pre‐ and post‐entrectinib treatment. Among evaluable pre‐treatment clinical samples ( N = 85), positive percentage agreements between F1L CDx and clinical trial assays (CTAs) were 47.4% ( NTRK fusions) and 64.5% ( ROS1 fusions); positive predictive value was 100% for both. The objective response rate for CTA + F1L CDx + patients was 72.2% in both cohorts. The median duration of response significantly differed between F1L CDx + and F1L CDx − samples in ROS1 ‐fp (5.6 vs. 17.3 months) but not NTRK ‐fp (9.2 vs. 12.9 months) patients. Fifteen acquired resistance mutations were detected. We conclude that F1L CDx is a clinically valid complement to tissue‐based testing to identify patients who may benefit from entrectinib and those with acquired resistance mutations associated with disease progression. Abstract : Entrectinib is a kinase inhibitor that targets both the NTRK and ROS1 oncogenes. We show that NTRK and ROS1 fusions are present in 46% and 64%, respectively, of blood samples from patients enrolled on a clinical trial, with a response rate of 72%. Profiling blood at progression showed that resistance occurs via mutations in NTRK / ROS1 or via downstream MAP‐kinase reactivation.